Satisfaction Of Healthcare Practitioners With The Work Environment And Its Relationship To The Quality Of Patient Care (The Review of Diabetic Studies, 2025)
This study focuses on the principle of satisfaction of the practitioners working at Prince Abdulaziz Bin Musaad Hospital and how this satisfaction relates to the quality of care given to patients. More specifically, the study aims to explore components of the work environment that may positively or negatively influence the satisfaction of practitioners and how this may impact patient outcomes. For this study, a descriptive cross-sectional methodology was utilised, and a convenience sample of 197 healthcare workers, which included nurses, doctors, and allied health personnel, was obtained and surveyed. This was achieved by administering a self-administered questionnaire that was pre-structured and included items pertaining to demographics, work environment, patient care quality, and the relationship that exists between these independent and dependent variables. The outcome demonstrated that the practitioners’ greatest satisfaction was with leadership support, teamwork, job security, and the work stoop. The only moderate concern was with the management of the work. Overall patient care was rated positively. This included satisfaction, accuracy, and communication of the patient, and all the professionalism, work care, and overall patient care satisfaction. Work environment satisfaction and patient care quality were linked positively through statistical analysis. Improvements on the availability of work resources, integrations of management, and teamwork were four variables that could enhance work outcomes. The study recommended that for improving satisfaction, the quantity of work and the quality of patient care, support from leadership, and work resources are necessary. Hospital administrators now have guidance on how to foster a supportive work environment that enables the delivery of optimally directed patient care.